Variation in size, protein, cyanide and tannin contents of lima bean (Phaseolus lunatus) - Offei, S.K.; Asante, I.K.; Danquah, E.Y. (Tropical Science, 2003)
Thirty one accessions had 100-seed weight of 23.8 to 71.8 g and protein contents from 20.4 to 30.3%. There was little variation in cyanide content. Tannin contents varied tenfold among the accessions and increased with colour.
Keywords: Cyanide; Lima bean; Protein; Tannin